Cognitive fluctuations of object recognition in Lewy body dementia: An EEG/MEG study: Neuroimaging / imaging and genetics. (7th December 2020) - Huang, Yujing
Abstract: Background: Lewy body dementia (LBD) shared a common pathological core feature of cognitive fluctuations. However, the clinical identification of attention fluctuation is still controversial. In this study, we combined EEG and MEG to explore the electrophysiological and magnetic biomarkers of attention fluctuations in LBD. We hypothesized that LBD showed stronger fluctuations in sensor‐level and source‐level EEG and MEG. Method: Nine LBD and twelve healthy controls (HC) were recruited in this study. We designed an object recognition task, in which an object stimulus appeared on the screen and then the participants were required to respond as quickly and accurately as possible to judge whether this object was an animal or not an animal. There were six blocks, each of which included 12 different animal stimuli and 12 non‐animal stimuli. The animal/non‐animal stimuli were repeated across blocks. EEG and MEG were simultaneously recorded online. Cognitive fluctuations were examined via the variations across all trials (trial‐wise fluctuations) or across blocks (block‐wise fluctuations). Result: (1) healthy controls had shorter reaction time and higher accuracy rate than LBD but the variations of reaction time was significantly higher in LBD than healthy controls. (2) HC had stronger overall EEG amplitudes for post stimulus in line with previous studies about the deficit of object recognition in dementia. The overall single‐trial‐wise variations and block‐wise variations of MAG/GRM were higher in LBD than HC. (3)Although time frequency power didn't showed significant differences between LBD and HC in most electrodes, lower theta phase lock value (PLV) in HC compared to LBD for central‐parietal EEG/MEG electrodes. The central‐parietal EEG/MEG PLV was significantly higher in HC than LBD for alpha, beta and gamma bands. (4) Interestingly, higher single‐trial‐wise phase‐lock values (PLV) variations in LBD compared to HC were mainly from theta band and alpha band for front‐parietal EEG/MEG electrodes. (5) The source localization results showed that trial‐wise and block‐wise source fluctuations in LBD had a tendency to involve a network of parietal areas, including postcentral gyrus, superial parietal areas et al. Conclusion: Our study revealed the possible biomarkers of attention fluctuations in LBD by using EEG and MEG.